ANTIOXIDANT ACTIVITY OF METHYL GALLATE ISOLATED FROM THE LEAVES OF Toona sureni - M. Taufik Ekaprasada; Hazli Nurdin; Sanusi Ibrahim; Dachriyanus Dachriyanus (Universitas Gadjah Mada, 2009)
An antioxidant compound has been isolated from the leaves of Toona sureni (Blume) Merr. The structure was determined to be methyl 3,4,5-trihydroxybenzoate (methyl gallate), based on UV-vis, FTIR, NMR and MS spectra. The isolated compound exhibited potent antioxidant activity in the α,α-diphenyl-β-picrylhydrazyl (DPPH) radical scavenging test, with IC50 value 1.02 μg/mL.